Mechanistically-guided advancement of photoinduced organocatalyzed atom transfer radical polymerization - Buss, Bonnie Leigh, author; Miyake, Garret, advisor; Bailey, Travis, committee member; Shi, Yian, committee member; Herrera-Alonso, Margarita, committee member (Colorado State University. Libraries, 2020)
Photoinduced organocatalyzed atom transfer radical polymerization (O-ATRP) is a promising polymerization methodology which leverages radical reactivity to afford macromolecular products with a high degree of control over polymer molecular weights and molecular weight distributions, paired with the added benefit of spatial and temporal control over polymerization. This process, a metal-free approach, relies on photoexcitation of an organic photoredox catalyst which stringently mediates the radical activation and deactivation steps of an oxidative quenching catalytic cycle. To successfully operate this cycle, and thus control the polymerization, the rate of deactivation must be faster than both the rates of radical activation and monomer propagation. Central to the initial development of O-ATRP has been the design and study of strongly reducing organic photocatalysts, particularly in the context of methacrylate monomer polymerizations. However, as a burgeoning methodology, the full scope of O-ATRP has not yet been established. In this dissertation, efforts in addressing three key challenges in O-ATRP, including reaction scalability, complex architecture synthesis, and polymerization of challenging monomers, through manipulation of features of the oxidative quenching mechanistic cycle is presented. To address these challenges diverse approaches were employed, including adaptation to continuous-flow reactors, implementation of multifunctional initiating systems, and rational design of a new family of organic photocatalysts, ultimately facilitating progression of O-ATRP to a scalable and efficient approach in the well-defined synthesis of industrially-relevant materials.
Keywords: photochemistry; catalysis; polymers